A term paper of strategic management for oral comprehensive examination - Yang, Yihang (Animo Repository, 1994)
This study of strategic management is being conducted for the company named Vision Garment Manufacturing, Inc. [not the real name of the company]. It presents the results and findings of the writer in helping the company determine the corporate objectives and develop strategies to achieve its objectives. The structure of the industry is analyzed to identify the external strategic factors (Opportunities and Threats) that are most important to the company's future. These include those elements or groups that directly affect and are affected by the company's operation. The competitors within the industry are categorized into strategic groups according to the similarity of their strategies. Each of the five forces from the competition environment are then evaluated to assess their probable impact on the company. The internal environment consist of variables (Strengths and Weaknesses) that are within the company itself. They form the context in which work is done. These include the corporate structure, culture and resources. The company's value-chain is analyzed in terms of the various functional steps involved in the production of the product or service. This is done to seek ways for the company to gain competitive advantage in the market place. The formulation of strategy is the development of long-range plans for the effective management of environmental opportunities and threats, in light of strengths and weaknesses of the company. It includes the corporate mission, specifying SMART objectives and developing strategies.The strategy of the company forms a comprehensive master plan stating how the company will achieve its mission and objectives. It maximizes the competitive advantage of the company.Corporate strategy explores the ways in which the company can develop a favorable portfolio strategy for its many activities. It is the pattern of decisions regarding the type of business in which the firm should be involved, the flow of financial and other resources to and from its divisions, the relationship of the corporation to key groups in its environment and the ways in which the firm can increase its profit. The functional strategy is the maximizing of resource productivity. Within the constraints of the corporate strategy, functional departments develop strategies in which their various activities and competence are pulled together for improvement of performance.